Fair Value as a Basis for Valuation of Biological Assets (Applied Study in the Al kafeel Co. For General Investments) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2020)
Biological assets, as assets used in enterprises engaged in agricultural activity and their importance worldwide, require accounting processes that are appropriate to the nature of these assets and their impact on natural and climatic conditions and factors. In light of the accounting standards for agricultural activity, fair value is used to assess biological assets rather than historical costs. Therefore, this research aims to identify what biological assets are, and the requirements for accounting for them according to fair value, and verify the determinants affecting the relationship between the Faithful Representation of information accounting for biological assets and fair value.Accordingly, a number of conclusions were reached:The specificity of agricultural activity necessitates the use of methods of accounting measurement that accompany the biological changes in animal and plant assets.The use of historical cost in the valuation of biological assets does not provide Faithful Representation financial information due to its omission of growth of biological assets as well as omission of market price changes.Therefore, the researcher recommended that the issuers of the accounting rules should update the Iraqi accounting base 11 (the historical cost) to conform to the latest amendments to the International Standard 41 (adopted for fair value),with a numerical example that can be adopted and applied in practice by various agricultural and animal production companies.